Microsoft 365 and SharePoint Online Cookbook - Ghatak, Sudeep (Packt Publishing, 2020)
Embrace modern solutions to enhance collaboration, teamwork, robotic process automation, and business intelligence in your organization using powerful Microsoft 365 services (formerly Office 365) Key Features Gain a complete overview of popular Microsoft 365 services using practical recipes and expert insights Collaborate with your team and external users effectively using SharePoint and Teams Create no-code and low-code solutions, such as bots, forms, dashboards, and workflows, using the Power platform Book Description Microsoft 365 in an integrated suite that provides intelligent tools for managing everyday organizational tasks like content management, communication, creating reports, and automating business processes. With this book, you'll get to grips with popular apps from Microsoft, with a focus on enabling workspace collaboration and productivity using Microsoft SharePoint Online, Teams, and the Power Platform to name a few. In addition to guiding you through the implementation of Microsoft 365 apps, this practical guide helps you to learn from a Microsoft consultant's extensive experience of working with the Microsoft business suite. Starting with a quick overview of the M365 ecosystem, the book covers recipes for implementing SharePoint Online for various content management tasks. You'll learn how to create sites for your organization and enhance collaboration across the business and then see how you can boost productivity with apps such as Microsoft Teams, Power Platform, Planner, Delve, and M365 Groups. Using a step-by-step approach, you'll also find out how to use the Power Platform efficiently, making the most of Microsoft PowerApps, Power Automate, PowerBI, and Power Virtual Agents. Finally, the book focuses on the SharePoint framework, which helps you to build custom Teams and SharePoint solutions. By the end of the book, you'll be equipped with the skills required to set up Microsoft 365 and SharePoint Online and be ready to enhance business productivity using a variety of tools. What you will learn Get to grips with a wide range of apps and cloud services in Microsoft 365 Discover ways to use SharePoint Online to create and manage content Store and share documents using SharePoint Online Improve your search experience with Microsoft Search Leverage the Power Platform to build business solutions with Power Automate, Power Apps, Power BI, and Power Virtual Agents Enhance native capabilities in SharePoint and Teams using the SPF...